고등학교 선택 교육과정 운영을 위한 온라인수업 제도화 방안 - 정영식(Youn-Sik Jeong) (한국콘텐츠학회 논문지, 14(3), 2014)
Due to a lack of teachers and available classrooms, high school students are not able to take the elective courses of their choice. In order to solve this problem with online instruction, I have used the following methods: First, I conducted a literature study to examine the concepts and models of online instruction. Second, I compared the number of students who took the CSAT subject tests with the number of students who enrolled in optional courses through KEDI's Education Statistics Services. Using the data gathered from this comparison, I could predict the demand for each optional course. Finally, I proposed amending the Elementary and Secondary Education Act; the Enforcement Decree of the Elementary and Secondary Education Act; the General Statement Curriculum of High Schools; and the Guidelines for Recording School through the expert interviews for on-line instruction in order to establish online instruction for high school students. 현재 고등학교에서는 교원 및 교실 부족 등으로 인해 학생들이 원하는 선택 과목을 수강하지 못하고 있다. 따라서 본 연구에서는 온라인수업을 통해 이러한 문제를 해결하고자 다음과 같은 내용을 연구하였다. 첫째, 문헌 연구를 통해 온라인수업의 개념과 모형을 연구하였다. 둘째, 교육통계분석시스템을 이용하여 과목별 개설 현황과 수능 응시 현황 자료를 비교하여 과목별 수요를 예측하였다. 셋째, 온라인수업을 고등학교에 정착시키기 위해서 초중등교육법과 동법 시행령, 고등학교 교육과정 총론(고시), 학교생활기록 작성 및 관리 지침(훈령)에 대한 개정 방안을 제시하였다. 관련 법령과 고시, 훈령에 대한 개정 방안은 온라인 수업 관계자, 시도교육청 담당자, 현장 교사로 구성된 전문가집단의 의견을 수렴하였다. 그 결과, 관련 법률과 지침의 개정 범위를 제시하였고, 온라인 수업에 대한 근거와 학사 운영 및 교육과정 운영 방안 제시, 온라인 수업에 참여할 교원의 자격과 배치 기준, 예산 확보 근거 등을 제시하였다.